Przesłanki odpowiedzialności za naruszenie obowiązków wynikających z pozwolenia na broń palną - Mikowski, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article presents general issues related to the conditions of legal liability for exceeding the rights and violation of obligations related to the authorisation of firearms, under the provisions governing access to firearms in Poland. The study includes both conditions for administrative liability and elements of criminal law regulation, which should be seen here as a supporting method that determines the issue in question. The Act of 21 May 1999 on firearms and ammunition, together with selected executive acts, was subjected to a synthetic analysis. The overall considerations include the types of legal liability in situations of the infringements in question; however, this part of the analysis is supplementary to the description of the causes of liability.
Keywords: pozwolenie na broń palną; broń palna; posiadanie broni palnej; bezpieczeństwo broni palnej